Getting started with Dynamics NAV 2013 application development a simple and practical guide to creating a relevant application for your company using Dynamics NAV 2013 /: a simple and practical guide to creating a relevant application for your company using Dynamics NAV 2013. (2013) - Unknown
No abstract available